Gereja sebagai Eksistensi Kerajaan Allah di Tengah Masyarakat - Roesmijati, Roesmijati; Salim, Eddy (STT Kingdom, 2025)
The existence of the church in general must be felt by the community. The church is a representative of the Kingdom of God on earth. The church has a role in completing the Great Commission and has an impact on community life. The role of the church is not only in spiritual matters but also in physical matters. This study aims to discuss the church as the existence of the kingdom of God in the midst of society. The purpose of this study is to provide motivation to believers that the existence of the church is fully responsible for the congregation and society both spiritually and physically.